Assessment of Regional Myocardial Uptake and Metabolism of ω-(p-123I-Phenyl) Pentadecanoic Acid with Serial Single-Photon Emission Tomography - Reske, S. N.; Biersack, H.-J.; Lackner, K.; Machulla, H.-J.; Kiiopp, R.; Hahn, N.; Winkler, C. (Nuklearmedizin - NuclearMedicine, 1982)
The utility of myocardial imaging and assessment of regional myocardial metabolism of ω-(123I-paraphenyl-)pen-tadecanoic acid (I-PPA) by means of serial single-photon tomography is demonstrated in animal experiments. High quality cross sectional images of dog hearts with clear delineation of left ventricular walls are obtained. Myocardial infarcts are visualized as areas of deficient radioactivity uptake. I-PPA elimination from non-infarcted myocardial regions is significantly (p < 0.001) prolonged when compared with unaffected controls. Hence, not only localized absence of uptake of free fatty acid by infarcted myocardium can be demonstrated with serial single-photon tomography but also general impairment of cardiac FFA-metabolism.